Form versus content in the comprehension of second language readind texts with the students of fourth level of english proficiency of the support center N 19 Coca - Salinas Valencia, Jorge Luis (2007)
Understanding second language acquisition (SLA) has been a topic of study for many years. Second language reading has been studied from many different perspectives such as the importance of first language transfer in learning to read in a Second Language, mental translation as a second language reading strategy, social influence of Second Language reading development, and understanding the limited knowledge of second language readers in relation to cultural and contextual factors. The purpose of this study is to investigate second language text comprehension from the perspective of language processing within the field of cognitive science, especially with reference to attention resources. The role of attention in second language acquisition with regard to the notion of detection is a crucial aspect of Second Language aural and written comprehension. As a function of attention, detection selects specific elements found in the input to be registered in working memory where they are subject to further processing by the Second language learner. During attention, more specifically detection, posits that form and meaning, which are not independent of one another, compete for the limited cognitive resources available to the adult Second language learner, especially, in the early stages of second language acquisition. Consequently, in these early stages, the demand of comprehending a message deplete the attention system making it more difficult for Second language learner to process for linguistic form and content or meaning at the same time. The overall purpose of this thesis is to determine the effect of attention to form versus attention to meaning while processing input for meaning during the advanced stage of second language acquisition. It includes conclusions and recommendations and the proposal, to be applied at the Support Center Nº 19 Coca...